A model for an early role of auxin in Arabidopsis gynoecium morphogenesis - Hawkins, Charles; Liu, Zhongchi (Frontiers in Plant Science, 2014)
The female reproductive organ of the angiosperm, the gynoecium, often consists of the fusion of multiple ovule-bearing carpels. It serves to produce and protect ovules and mediate pollination. The gynoecium has likely contributed to the tremendous success of angiosperms over their 160 million year history. In addition, being a highly complex plant organ, the gynoecium is well suited as a model system for investigating plant morphogenesis and development. The longstanding model of gynoecium morphogenesis in Arabidopsis holds that apically-localized auxin biosynthesis in the gynoecium results in an apical to basal gradient of auxin that serves to specify along its length the development of stigma, style, ovary, and gynophore in a concentration-dependent manner. This model is based primarily on the observed effects of the auxin transport blocker N-1-naphthylphthalamic acid (NPA) as well as analyses of mutants of Auxin Response Factor 3/ETTIN (ETT). Both NPA treatment and ett mutation disrupt gynoecium morphological patterns along the apical-basal axis. More than a decade after the model's initial proposal, however, the auxin gradient on which the model critically depends remains elusive. Furthermore, multiple observations are inconsistent with such an auxin-gradient model. Chiefly, the timing of gynoecium emergence and patterning occurs at a very early stage when the organ has little-to-no apical-basal dimension. Based on these observations and current models of early leaf patterning, we propose an alternate model for gynoecial patterning. Under this model, the action of auxin is necessary for the early establishment of adaxial-abaxial patterning of the carpel primordium. In this case, the observed gynoecial phenotypes caused by NPA and ett are due to the disruption of this early adaxial-abaxial patterning of the carpel primordia. Here we present the case for this model based on recent literature and current models of leaf development.